Shaping MOF oxime oxidation catalysts as three-dimensional porous aerogels through structure-directing growth inside chitosan microspheres. Issue 11 (16th May 2022) - Hammi, Nisrine; Chen, Shuo; Primo, Ana; Royer, Sebastien; Garcia, Hermenegildo; El Kadib, Abdelkrim
Abstract : MOF-based recyclable catalysts can be grown and shaped as porous aerogels using chitosan microspheres. Abstract : Metal–organic frameworks stand as unique building blocks, bridging the gap between coordination chemistry and materials science. While significant advances have been made in their design, current efforts focus on expanding their pore size above the microporous regime and on their shaping into well suitable end use devices. For such a purpose, we herein explored the use of chitosan hydrogel microspheres as a mold to grow an extended network of MOFs, followed by CO2 -supercritical drying to generate three-dimensional polysaccharide nanofibrils embedding entangled MOF nanoclusters. This strategy was found to be highly versatile, and allows for shaping HKUST-1, ZIF-8, ZIF-67 and Fe-BTC inside chitosan microspheres. The resulting lightweight aerogels display excellent activity for oxime oxidation, with HKUST-1 loaded on chitosan beads standing as the most promising. The virtues of supercritical drying were substantiated by comparing the catalytic activity of these aerogels with their xerogel analogues as well as pristine HKUST-1. Interestingly, moreover, the configuration of MOFs in chitosan beads precludes the metal from leaching and allows easy recovery of the catalyst from the medium and its possible recycling.